INTEGRATING RESPONSIBLE AI IN ABUSE HELPLINE CONTACT CENTERS: A FRAMEWORK FOR ETHICAL IMPLEMENTATION AND HUMAN-CENTERED SUPPORT - Santhosh Kumar Ganesan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the integration of Artificial Intelligence (AI) technologies in abuse helpline contact centers, presenting a comprehensive framework for ethical implementation that prioritizes technological innovation and human-centered support. The article identifies critical considerations in AI deployment, analyzing existing literature and operational case studies, including privacy protection, bias mitigation, and emotional intelligence integration. The article establishes a novel human-AI collaboration model that emphasizes AI as a supportive tool rather than a replacement for human operators, incorporating real-time assistance capabilities while maintaining essential human oversight. Our article demonstrates that successful implementation requires a carefully balanced approach incorporating four key elements: (1) robust ethical guidelines for data handling and decision-making transparency, (2) clear protocols for AI-human collaboration that preserve the primacy of human empathy, (3) comprehensive safety and accountability measures, and (4) adaptable frameworks for emotional intelligence integration. The article concludes with practical recommendations for implementation, addressing regulatory compliance, training requirements, and quality assurance measures. These findings contribute to the growing body of literature on responsible AI implementation in sensitive support services while providing actionable insights for organizations seeking to enhance their abuse helpline operations through technological innovation without compromising the human-centered nature of crisis support.